Approaches to the evaluation of lip hyperpigmentation - Vasanop Vachiramon (2018)
Hyperpigmentation of the lips is a common condition. It is associated with a wide variety of conditions that include physiologic changes, genodermatoses, inflammatory diseases, endocrinologic disorders, drugs and chemicals, benign and malignant neoplasm, and other non-melanotic conditions. The aim of this article is to provide a clinical approach to hyperpigmented lesions on the lips based on the extent of lesions, the age of onset, and associated systemic involvements. In this review, we present an algorithm to guide the diagnosis of and plan for therapeutic intervention for pigmented lesions of the lips. The algorithm is based on the typical clinical presentation of each entity and should not be taken as an absolute indicator of diagnosis. Although the differences in color can help to differentiate among pigmented lesions, the interpretation of color can be subjective and is influenced by the amount and location of the pigment within the mucosa. The limitations of this review are that some data are based on case reports and small case series that may not reflect true association. © 2012 The International Society of Dermatology.